International trade agreements and trade policy issues: essays on Barbados - Woodroffe, Louis St. Elmo (2002)
The objective of this study is to examine a series of trade policy issues related to Barbados' participation in multilateral, hemispheric and regional trade agreements. The three trade policy issues examined are (1) WTO Agreements and the trade policy preferences of firms, (2) preferential trade agreements and the export performance of firms, and (3) the selection of sensitive sectors to be excluded from free trade under international trade agreements. The first essay investigates support of manufacturers in Barbados for WTO rules. Based on the results of a trade policy survey, the study revealed that in general, there is support for multilateral trade rules. OLS and ordered probit regression found that there is evidence that export performance, competitiveness perceptions, and to a lesser extent external association, influence firms to support liberalisation. Capacity under-utilisation, and surprisingly diversification, lower firm's support for liberalisation. The second study examines the importance of preferential trade agreements to the export performance of firms in Barbados. The trade policy survey found that 91% of exporting firms, and 80% of exports benefit from trade preferences. OLS and tobit regression show that factor endowments, economies of scale and technology are important in fashioning export performance. The analysis also show that while trade preferences and external association have a positive impact on export performance, wage costs and protection in both local and foreign markets have a negative impact. The third essay examines the factors influencing the sensitivity of sectors and their exclusion from free trade under the provisions of hemispheric trade agreements. OLS and probit regression analysis suggest that maintenance of the status quo, adjustment costs minimisation, and considerations about fair trade influenced the selection process. Overall, the findings of the studies support theoretical and empirical work in the respective areas, thereby indicating that similar models developed within the context of industrial economies, are applicable in large measure to developing and small developing economies. In terms of policy implications, the studies pointed to the need for government to focus more on international trade competitiveness strategies in order to fully benefit from the opportunities offered by international trade agreements.